Contexts and constructs: Implications for the testing of listening in pilots’ communication with air traffic controllers - Garcia, Angela Carolina de Moraes; Fox, Janna (The ESPecialist, 2023)
The International Civil Aviation Organization (ICAO) published the Language Proficiency Requirements for pilots and air traffic controllers (ATCOs) in 2003. Research has shown that there is still a lack of clarity regarding what needs to be assessed in terms of the English used by pilots and ATCOs in radiotelephony (DOUGLAS, 2014; EMERY, 2014; KIM; BILLINGTON, 2016; KIM; ELDER, 2015; MONTEIRO, 2019; READ; KNOCH, 2009). The purpose of the present study was to investigate the nature of the listening tasks performed by pilots as an essential step in test development and validation. This explanatory sequential mixed-methods study (CRESWELL, 2015), elicited questionnaire responses from 156 pilots (Phase 1) and subsequently interviewed six aeronautical English experts (Phase 2) to better understand the characteristics of the listening tasks that pilots undertake during radiotelephony communications. Quantitative and qualitative data were analysed, and findings were merged. They provide information that may usefully inform the development of the listening test construct and the test specifications.